Single- and two-stage fan designs for a supersonic airliner with focus on certification noise reduction - Graebert, Matti; Jaron, Robert; Villena Munoz, Cristina; Plohr, Martin; Moreau, Antoine (American Institute of Aeronautics and Astronautics (AIAA), 2025)
A comprehensive analytical approach is taken to compare the aerodynamic performance as well as the landing and take-off noise of a single and a two-stage fan at pre-design level. The fans were designed for the engines of a supersonic airliner with the goal of minimizing noise certification levels. The prediction of aerodynamic performance is performed for on- and off-design points using analytical and semi-empirical models, the noise for landing and take-off operations is calculated using analytical approaches in modelling noise sources and propagation to the certification points. Certification metrics are also calculated and used in this comparison. This process is run for both fan designs on a baseline take-off trajectory in accordance with current regulations, as well as an optimized trajectory exploiting potential regulation changes for supersonic aircraft. With this study, the authors are able to demonstrate that a two-stage fan design produces significantly lower noise levels. In configurations and on trajectories on which fan noise is dominant, significantly lower certification levels could be achieved.
Keywords: 40 Engineering; 49 Mathematical Sciences; 4001 Aerospace Engineering